Relationship Ki-67 and BCL-2 in gastrointestinal lymphomas - Hatice E. PEŞDERELİ and Kemal H. GÜLKESEN and Gülgün ERDOĞAN and Mustafa T. GELEN and Gülten KARPUZOĞLU and İnci SÜLEYMANLAR and Canan F. SARGIN (Turkish Journal of Gastroenterology, 2019)
-